GP2Y1010AU0F Sensor as Dust Particle Measurement Device: Literature Study on its Efficiency and Application - I Made Dwi Pramana Putra; Eva Darnila; Tonny Wahyu Aji (Journal of Computation Physics and Earth Science (JoCPES), 2024)
Air pollution is an environmental problem that negatively impacts humans and the environment. An air quality monitoring system is required to track the effects of particulate matter (PM), one of the factors that contributes to air pollution. Accurate monitoring equipment is generally expensive and difficult to maintain, so low-cost sensors such as the GP2Y1010AU0F are used as a solution for air quality measurement. This literature review evaluates the efficiency and potential application of the GP2Y1010AU0F sensor by analyzing 20 relevant studies. Based on the review conducted, the GP2Y1010AU0F sensor shows acceptable sensitivity, moderate repeatability, and low error values when measuring air quality. It also showed a good level of correlation with similar devices. The sensor's small size, affordability, and compatibility with microcontrollers make it adaptable to system integration and development into applications and web-based monitoring. However, mass production leads to inconsistency and a reduction in the measurement accuracy of the device. It can be concluded that the GP2Y1010AU0F sensor has potential as a low-cost air quality monitoring equipment with extensive development potential despite its limitations.